Crude Contempt: Examining Local Pushback to Oil and Gas Development in California. Issue 2 (23rd March 2021) - Mahafza, Zachary; Fisk, Jonathan M.; Adams, David P.
Abstract : Investigating voter preferences has been a challenge for those studying the politics of fracking. Recent scholarship has assessed local fracking bans in Texas, Ohio, Colorado, and Pennsylvania. These findings suggest the importance of political ideology and voters' experience. This project continues to develop an understanding of local defiance and "fracking" attitudes, by extending this inquiry to California. Utilizing a novel dataset of over 400 voting precincts across three California counties, we find that political ideology, the presence of nearby spills, and education shape voters support for local bans on fracking. Related Articles: Ash, John S. 2011. "Radiation or Riots: Risk Perception in Nuclear Power Decision Making and Deliberative Approaches to Resolving Stakeholder Conflict." Politics & Policy 39 (2): 317‐344. https://doi.org/10.1111/j.1747‐1346.2010.00237.x Fisk, Jonathan M., Charles Davis, and Benjamin Cole. 2017. "'Who Is at Fault?' The Media and the Stories of Induced Seismicity." Politics & Policy 45 (1): 31‐50. https://doi.org/10.1111/polp.12193 Neill, Katharine A., and John C. Morris. 2012. "A Tangled web of Principals and Agents: Examining the Deepwater Horizon oil Spill through a Principal‐Agent Lens." Politics & Policy 40 (4): 629‐656. https://doi.org/10.1111/j.1747‐1346.2012.00371.x Abstract : Desprecio del crudo: Examinando el retroceso local al desarrollo de petróleo y gas en California: Investigar las preferencias de los votantes ha sido un desafío para quienes estudian la política del fracking. Una beca reciente ha evaluado las prohibiciones locales de fracturación hidráulica en Texas, Ohio, Colorado y Pensilvania. Estos hallazgos sugieren la importancia de la ideología política y la experiencia de los votantes. Este proyecto continúa desarrollando una comprensión del desafío local y las actitudes del "fracking, " al extender esta investigación a California. Utilizando un nuevo conjunto de datos de más de 400 distritos electorales en tres condados de California, encontramos que la ideología política, la presencia de derrames cercanos y la educación dan forma al apoyo de los votantes a las prohibiciones locales del fracking. Abstract : 反对原油：加州石油天然气开发遭遇的地方抵制分析: 研究选民偏好对那些研究水力压裂政治的人士而言一直是一项挑战，近期学术评估了德克萨斯州、俄亥俄州、科罗拉多州和宾夕法尼亚州的地方水力压裂禁令。这些研究发现暗示了政治意识形态和选民经历的重要性。本文通过研究加利福尼亚州，继续对地方抗议及"水力压裂"态度加以理解。通过使用一个包含该州三县400个选区的独特数据集，我们发现，政治意识形态、附近油气泄露的出现、以及教育程度影响了选民对地方水力压裂禁令的支持。